Application of the Phillips curve in EU - Šťastná, Zuzana (2020)
This thesis aims to explore the validity of the Phillips curve in the EU between 2000 and 2019. Using the simple linear regression model, we discover the relationship between the rate of unemployment and the inflation rate in four different EU countries and we determine whether it corresponds to the theory described by A. W. H. Phillips in 1958. We examine the nature, shifts, and slope of constructed curves together with the Okun’s law interpreted as an additional aspect to the overall analysis. Our results suggest that the relationship between inflation and unemployment rates is positive in two analysed countries between 2000 and 2006 which directly contradicts Phillips’ theory. Additionally, we discover the importance of cost factors and ineffective labour market policies and their harmful effect on the accuracy of the Phillips curve model.